Teaching Students of Higher Educational Institutions Oral Monologue Speech in English - Lysak, Halyna; Martynyuk, Olena (Pedagogical Discourse, 2019)
The article deals with the problem of efficient ways of teaching monologue speech in English with the help of feature films. The essence of the notion «monologue speech», the main types and peculiar features of monologue utterance have been analysed. The main tendencies of teaching oral monologue speech have been examined. Two main ways have been defined: the first one is «from the top to the bottom», it’s when the monologue skills are formed on the basis of the text; and the second one is when the monologue skills are formed without any aids or texts. The scientists discover three steps in the process of development of monologue skills and according to these steps there are three groups of exercises: the first group consists of the exercises for combining the sentences into super phrasal units; the exercises of the second group are aimed to teach mini monologues and the last one is to teach different types of monologues. The use of feature films as the basis for forming students’ oral monologue skills has been analyzed. The advantages of videophonogram usage in teaching monologue speech have been defined. They are: demonstration of objects, parts of the living, interesting events that evoke positive students’ emotions. The demonstration of feature films gives the possibility to use motivational factors in teaching monologue speech in English, stimulate verbal communication, stimulate motivation and demonstrate the authentic speech patterns. The work with the authentic feature films gives the possibility: to teach oral monologue speech in English when the students speak in the role of the main characters after watching a film; to teach to speak English in the process of demonstration of the parts of the film; to teach spontaneous monologue speech after watching a film using different types of monologues.